BS EN IEC 61097-2. Global maritime distress and safety system (GMDSS). Part 2. COSPAS-SARSAT EPIRB. Satellite emergency position indicating radio beacon operating on 406 MHz. Operational and performance requirements, methods of testing and required test results (10th January 2020) - British Standards Institution,
No abstract available